Disease and weight loss: a prospective study of middle-aged and older adults in Costa Rica and England - Laura Blue; Noreen Goldman; Luis Rosero-Bixby (Instituto Nacional de Salud Pública, 2015)
Objective. To determine whether disease predicts weight loss in population-based studies, as this may confound the relationship between weight and mortality. Materials and methods. We used longitudinal data from the Costa Rican Longevity and Healthy Aging Study (CRELES) and the English Longitudinal Study of Ageing (ELSA). We defined two overlapping outcomes of measured weight loss between waves: >1.0 point of body mass index (BMI) and >2.0 BMI points. Logistic regression models estimated the associations with disease, adjusting for age (range 52-79), sex, smoking, and initial BMI. Results. In ELSA, onset of diabetes, cancer, or lung disease is associated with loss >2.0 points (respectively, OR=2.25 [95%CI: 1.34-3.80]; OR=2.70 [95%CI: 1.49-4.89]; OR=1.82 [95%CI: 1.02-3.26]). In CRELES, disease-onset reports are not associated with weight loss at 5% significance, but statistical power to detect associations is poor. Conclusion. Although it is known that some diseases cause weight loss, at the population level these associations vary considerably across samples.